Direct genital manipulation is rare a manifestation of childhood gratification behaviour below 5 years of age: A case series - Biswas, Biswajit; Laha, Sumanta; Sil, Archan; Das, Mousumi; Mondal, Shibnath; Kumar, Raveesh; Biswas, Priyanka; Sarkar, Santi (Asian Journal of Medical Sciences, 2020)
Childhood masturbation/self-gratification behaviour means self-stimulation of the genitals by an immature child. Literature on this topic is scarce and scattered. Though most of the paediatricians seem to know about this entity, precise knowledge on spectrum of different behavioural patterns these children may show is lacking. Masturbatory activity in infants and young children is difficult to recognise because it often does not involve manual stimulation of the genitalia at all. We hereby report a series of 3 cases of childhood masturbation where direct genital manipulation, a very rare manifestation, was evident during gratification spells.